2001
DOI: 10.1111/j.1752-7325.2001.tb03380.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Knowledge and Opinions Among Maryland Nurse Practitioners

Abstract: The reported knowledge of oral cancer, in conjunction with opinions about level of knowledge and training, point to a need for systematic educational updates in oral cancer prevention and early detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…However, a series of surveys of intensive care nurses (Ganz et al, 2009), staff nurses (Adams, 1996), and nurse practitioners (Sirphant, Drury, Horowitz, & Harris, 2001) showed that the majority of the nurses surveyed had limited knowledge about the risk factors and signs and symptoms of OPC. They felt inadequately trained or uncomfortable examining the oral cavity and did not consider oral health screening to be their responsibility.…”
Section: Knowledge Attitudes and Practices Of Baccalaureate Nursingmentioning
confidence: 99%
“…However, a series of surveys of intensive care nurses (Ganz et al, 2009), staff nurses (Adams, 1996), and nurse practitioners (Sirphant, Drury, Horowitz, & Harris, 2001) showed that the majority of the nurses surveyed had limited knowledge about the risk factors and signs and symptoms of OPC. They felt inadequately trained or uncomfortable examining the oral cavity and did not consider oral health screening to be their responsibility.…”
Section: Knowledge Attitudes and Practices Of Baccalaureate Nursingmentioning
confidence: 99%
“…11 Therefore, a statewide initiative was begun in Maryland to better understand and address this health problem. 12 As a part of this initiative, health care providers in the state including dentists, 13 dental hygienists, 14 nurse practitioners, 15 and physicians 16 were assessed with respect to their knowledge and opinions regarding oral cancer. The survey of Maryland general dentists revealed that they did not have adequate knowledge regarding the risk factors for or the signs and symptoms of oral cancer.…”
mentioning
confidence: 99%
“…[17][18][19] A copy of the questionnaire is available on request from the authors. The following measures were included in this study:…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, previous studies 16,17 have shown that oral cancer attracted little attention among nurse practitioners: They did not routinely examine patients for oral lesions, most of them felt that their knowledge of oral cancer was not current, and few of them felt that oral cancer was a public health problem. The factors underlying this low prioritization are not yet clear.…”
mentioning
confidence: 93%